"Black Boys: Invisible to Visible": A Psychoeducational Group Fostering Self-Efficacy, Empowerment, and Sense of Belonging for African American Boys. Issue 3 (2nd July 2020) - Challenger, Clewiston D.; Duquette, Kevin; Pascascio, Domonique
ABSTRACT: Far too often African American boys are negatively portrayed in the media and are labeled as at-risk and violent. These labels impact perceptions within public schools. They also decrease self-efficacy, lower academic motivation, and lessen attachment to the school and community. We conceptualized a psychoeducational group for African American adolescent boys, Black Boys: Invisible to Visible (BBI2V), aimed at improving these areas. BBI2V presents a group counseling curriculum focused on three themes: making positive choices, speaking one's truth, and developing personal worth. A case illustration is provided to examine how a student may benefit from the BBI2V experience. Implications for practitioners are provided.